A smooth vetch (Vicia villosa var.) strain endogenous to the broad-spectrum antagonist Bacillus siamensis JSZ06 alleviates banana wilt disease - Ruan, Yan-Nan; Nong, Caihong; Jintrawet, Attachai; Fan, Huacai; Fu, Libo; Zheng, Si-Jun; Li, Shu; Wang, Zhi-Yuan (Frontiers in Plant Science, 2024)
Fusarium oxysporum f. sp. cubense Foc Tropical RACE 4 is the pathogen responsible for the disastrous banana disease Fusarium wilt, which is extremely difficult to control. Biological control strategies are considered as an environmental-friendly approach for disease management. Green manure, known for its ability to maintain and improve soil fertility and quality, is commonly utilized in southwestern China, with smooth vetch being a popular cover crop. However, the potential of smooth vetch as a biological control agent for banana wilt remains largely unexplored. In the present study, antagonistic Bacillus siamensis JSZ06 screened from smooth vetch and extracts of the fermentation broth of its strains had strong antifungal effects against Foc TR4 in vitro, with inhibition rates of 70.20% and 70.56%, respectively. A pot experiment proved that JSZ06 also has a strong in vivo antifungal activity. It can suppress the infestation of 'Baxi' banana (Musa spp. AAA) plants with Foc TR4 pathogen filaments effectively, with a control effect of 76.71% to 79.25%, and can significantly promote the seedling vigor and growth of banana. The strain JSZ06 was identified as B. siamensis. Extracts of B. siamensis JSZ06 inhibited both Foc TR4 growth as well as spore germination by disrupting the integrity of the cell membrane and the fungal ultrastructure. Notably, the strain and its extracts exhibited a broad-spectrum antifungal potency against all 10 selected phytopathogenic fungi and possessed 12 pairs of synthase genes associated with antifungal activity and phytohormone synthesis. Excavation of the growth-promoting potential of strain JSZ06 revealed that JSZ06 is capable of producing IAA, iron carrier, ACC deaminase, solubilizing inorganic phosphorus as well as potassium, and has a high growth-promoting potential. To our knowledge, this is the first study that provides a scientific basis for the use of B. siamensis JSZ06 in the field of banana wilt bio-prophylaxis.